KIF5A regulates axonal repair and time-dependent axonal transport of SFPQ granules and mitochondria in human motor neurons - Irune Guerra San Juan; Jessie W. Brunner; Kevin Eggan; Ruud F. Toonen; Matthijs Verhage (Neurobiology of Disease)
Mutations in the microtubule-binding motor protein kinesin 5 A (KIF5A) are implicated in several adult-onset motor neuron diseases, including Amyotrophic Lateral Sclerosis, Spastic Paraplegia Type 10 and Charcot-Marie-Tooth Disease Type 2. While KIF5 family members transport a variety of cargos along axons, the specific cargos affected by KIF5A mutations remain poorly understood. Here, we generated KIF5Anull mutant human motor neurons and analyzed the impact on axonal transport and motor neuron outgrowth and regeneration in vitro. KIF5A deficiency caused reduced neurite complexity in young neurons (DIV14) and defects in axonal regeneration. KIF5A deficiency did not affect neurofilament transport but impaired mitochondrial motility and anterograde speed at DIV42. Notably, KIF5A deficiency strongly reduced anterograde transport of splicing factor proline/glutamine-rich (SFPQ)-associated RNA granules in DIV42 axons. Hence, KIF5A plays a critical role in promoting axonal regrowth after injury and in driving the anterograde transport of mitochondria and especially SFPQ-associated RNA granules in mature neurons.